Re-shaping graphene hydrogels for effectively enhancing actuation responses. Issue 29 (1st July 2015) - Xue, Jiangli; Hu, Chuangang; Lv, Lingxiao; Dai, Liming; Qu, Liangti
Abstract : Based on a newly-developed re-shaping strategy, graphene/polypyrrole hybrid hydrogel with controllable structure has been constructed, which works as actuator having a maximum strain response of up to 13.5% under a low voltage stimulation of 0.8 V. Abstract : The development of actuation-enabled materials is important for smart devices and systems. Among them, graphene with outstanding electric, thermal, and mechanical properties holds great promise as a new type of stimuli-responsive material. In this study, we developed a re-shaping strategy to construct structure-controlled graphene hydrogels for highly enhanced actuation responses. Actuators based on the re-shaped graphene hydrogel showed a much higher actuation response than that of the common graphene counterparts. On the other hand, once composited with a conducting polymer ( e.g., polypyrrole), the re-shaped hybrid actuator exhibits excellent actuation behavior in response to electrochemical potential variation. Even under stimulation at a voltage as low as 0.8 V, actuators based on the re-shaped graphene-polypyrrole composite hydrogel exhibit a maximum strain response of up to 13.5%, which is the highest value reported to date for graphene-based materials.